Upaya Peningkatan Produktivitas melalui Proyek Continuous Improvement pada Line Y di PT. Z - Isaiah Thomas Joyodiono; Herri Christian Palit (Jurnal Titra, 2022)
PT. Z is one of the largest tobacco producing companies in Indonesia, as a company that has the spirit of continuous improvement, the company wants to continue to increase their productivity, which is measured by yield and labor productivity. This research was conducted to provide suggestions as an effort to increase yield and labor productivity. In the project of eliminating idle time for the rotary dryer, it was carried out by rotating workers and adding workers from other lines, the result shows there was a significant increase in labor productivity. In the cleaning process, a suggestion was given in the form of the method used, which initially used the blow method to the suction method. In the metal detecting process, it is proposed to place a magnet before the raw material passes through the metal detector machine, this is expected to reduce overprocessing waste by 25 to 37.5 minutes or 625 to 937.5 kilograms. To determine machine parameters that affect yield, multiple linear regression analysis was performed. Based on these results, it was found that there were 4 variables. which significantly affects the yield for product 1. Meanwhile for product 2, there were 5 variables that significantly affect yields.